Прогнозирование абразионных процессов водохранилищ Беларуси методом природных аналогов - Kobyak Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The hydrological conditions changing at existing reservoirs affects different processes development: marginal erosion, water logging zones, offshore strip vegetable kingdom changing, etc. The bank line reformation is one of the most dangerous. The marginal erosion processing prognosis based on the natural analogue method with similarity criteria usage is offered in the paper. Morphological, geological and hydrological similarities between the analogue object and predicted object are taken into account.